Phosphorus-nitrogen synergistic acrylate monomer, phosphorus-nitrogen-fluorine-containing polyacrylate water-repellent flame-retardant finishing agent and preparation method of phosphorus-nitrogen-fluorine-containing polyacrylate water-repellent flame-retardant finishing agent

By synthesizing phosphorus and nitrogen synergistic acrylate monomers and fluorine-containing monomers at low temperature, a finishing agent with both flame retardant and water-repellent functions was prepared. This solved the problems of complex preparation and difficult operation of flame retardants in the existing technology, and achieved a high-efficiency and environmentally friendly improvement in flame retardant performance.

CN120865292APending Publication Date: 2025-10-31DONGHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510866872.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-26
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

The preparation conditions of existing phosphorus-nitrogen synergistic flame retardants are complex, and DOPO is complicated to operate in cotton fabric finishing, making it difficult to effectively improve the flame retardant properties of cotton fabrics.

Method used

A phosphorus-nitrogen synergistic acrylate monomer was synthesized by low-temperature reaction and then polymerized in a one-pot solution with fluorinated monomers, crosslinking monomers, and soft monomers to prepare a phosphorus-nitrogen fluorinated polyacrylate water-repellent and flame-retardant finishing agent with both flame-retardant and water-repellent functions.

Benefits of technology

It achieves halogen-free, environmentally friendly, and highly efficient flame retardant effects, improves the durability and chemical bonding strength of the finishing agent, reduces the amount and cost of flame retardant, and also has water-repellent properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120865292A_ABST
    Figure CN120865292A_ABST
Patent Text Reader

Abstract

The invention relates to a phosphorus-nitrogen synergistic acrylate monomer, a phosphorus-nitrogen-fluorine-containing polyacrylate water-repellent flame-retardant finishing agent and a preparation method of the phosphorus-nitrogen synergistic acrylate monomer and the phosphorus-nitrogen-fluorine-containing polyacrylate water-repellent flame-retardant finishing agent, the structure of the phosphorus-nitrogen synergistic acrylate monomer is shown as a formula (I), in the formula, R1 comprises any one of methoxyl, ethyoxyl, hydroxyl, phenyl, phenoxyl and spiro hydrocarbon; r2 comprises an alkylene group of C2-C6; and the DOPO is 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and the general formula of the DOPO is shown in the description. The phosphorus-nitrogen-fluorine-containing polyacrylate water-repellent flame-retardant finishing agent disclosed by the invention is prepared by reacting a phosphorus-nitrogen synergistic acrylate monomer with a fluorine-containing monomer, a crosslinking monomer and a soft monomer. The preparation method of the phosphorus-nitrogen synergistic acrylate monomer flame retardant is simple, halogen is not contained, the environment-friendly requirement is met, and the flame-retardant effect of a finishing agent is improved; meanwhile, the copolymer is formed in a grafting block form, so that the durability of the flame retardant is improved, and the functionality of the finishing agent and the chemical binding force of the finishing agent to a base material are also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of flame retardants, and specifically relates to a phosphorus-nitrogen synergistic acrylate monomer, a phosphorus-nitrogen fluorine polyacrylate water-repellent flame retardant finishing agent, and its preparation method. Background Technology

[0002] Cotton fabrics, with their excellent biodegradability, breathability, and comfort, have become an indispensable natural textile material in the clothing and home furnishing industries. However, untreated cotton fabrics have a limiting oxygen index (LOI) of only about 18%, making them highly flammable when exposed to open flames. Their natural hydrophilic properties also cause them to easily absorb pollutants, severely limiting their application in high-safety scenarios such as interior decoration, automotive interiors, and fire protection. Among the flame retardants currently researched, halogenated flame retardants are the most effective and produced in the largest quantities, but they produce toxic gases during combustion, harming the environment and human health. Phosphorus-based flame retardants offer good flame retardancy, are environmentally friendly, and have low toxicity, making them the best alternative to halogenated flame retardants. Combining phosphorus-based flame retardants with other flame retardants can further improve their flame retardant performance. 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), as an organophosphorus flame retardant, is widely used in the flame retardancy of materials such as polycarbonate and epoxy resins due to its good thermal stability, halogen-free nature, low toxicity, and low smoke. However, its application in fabric finishing, especially in cotton fabric finishing, is still rare. The PH bond in the DOPO structure is highly reactive to olefins, epoxy bonds, and carbonyl groups. Current research suggests that incorporating DOPO into cotton fabrics through reactions with these groups can increase the LOI (Lower Oxygen Intake) to 24-40%. However, these reactions typically require high temperatures or even specific catalysts, increasing the complexity of the operation. Summary of the Invention

[0003] The technical problem to be solved by the present invention is to provide a phosphorus-nitrogen synergistic acrylate monomer, a phosphorus-nitrogen fluorine polyacrylate water-repellent flame retardant finishing agent and its preparation method, overcoming the limitations of existing phosphorus-nitrogen synergistic flame retardant preparation conditions and the complexity of operation.

[0004] This invention provides a phosphorus-nitrogen synergistic acrylate monomer, the structure of which is shown in formula (1):

[0005]

[0006] Wherein, R1 includes any one of methoxy, ethoxy, hydroxy, phenyl, phenoxy, and spirocyclic hydrocarbons; R2 includes C2 to C6 alkylene compounds; and DOPO is 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

[0007] Preferably, the phosphorus-nitrogen synergistic acrylate monomer is prepared by reacting a DOPO-containing amine compound with a phosphoric acid chloride-containing methacrylate compound; wherein the structure of the DOPO-containing amine compound is shown in formula (II):

[0008]

[0009] The structure of the phosphoryl chloride-containing methacrylate compound is shown in (III):

[0010]

[0011] More preferably, the phosphorus-nitrogen synergistic flame-retardant acrylate monomer is 2-(((4-(6-oxodibenzo[c,e][1,2]oxaphosphine-6-yl)piperazine-1-yl)(phenyl)phosphonyl)oxy)ethyl methacrylate (PPN), with the following structural formula:

[0012]

[0013] The present invention provides a method for preparing the above-mentioned phosphorus-nitrogen synergistic acrylate monomer, comprising: dissolving the DOPO-containing amine compound and the phosphoric acid chloride-containing methacrylate compound in a solvent, reacting at -10 to 0°C for 2 to 24 hours, and separating to obtain the phosphorus-nitrogen synergistic acrylate monomer.

[0014] Preferably, the molar ratio of the DOPO-containing amine compound to the phosphoryl chloride-containing methacrylate compound is 1:1 to 2.

[0015] More preferably, the molar ratio of the DOPO-containing amine compound to the phosphoryl chloride-containing methacrylate compound is 1.0:1.0-1.5.

[0016] Preferably, the volume-to-mass ratio of the solvent to the total amount of the DOPO-containing amine compound and the phosphoryl chloride-containing methacrylate compound is 2–10 ml / g.

[0017] Preferably, the solvent includes any one of substituted alkanes, esters, ethers, and nitriles.

[0018] Further, the solvent includes any one of dichloromethane, 1,2-dichloroethane, trichloromethane, carbon tetrachloride, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, isopropyl acetate, isobutyl acetate, amyl acetate, diethyl ether, propyl ether, isopropyl ether, butyl ether, acetone, butanone, cyclohexanone, acetonitrile, and propionitrile.

[0019] More preferably, the solvent is any one of dichloromethane, ethyl acetate, acetone, and propionitrile.

[0020] Preferably, the separation method includes, but is not limited to, any one of distillation, filtration, and column chromatography.

[0021] This invention provides a phosphorus-nitrogen-fluorine polyacrylate water-repellent and flame-retardant finishing agent, which is prepared by reacting the above-mentioned phosphorus-nitrogen synergistic acrylate monomer with fluorine-containing monomer, crosslinking monomer and soft monomer.

[0022] Preferably, the fluorinated monomer includes, but is not limited to, any one of trifluoroethyl methacrylate, 2-(perfluorooctyl)ethyl methacrylate, 2-(perfluorohexyl)ethyl methacrylate, 2-(perfluorobutyl)ethyl methacrylate, 1,1,1,3,3,3-hexafluoroisopropyl isobutylene acrylate, and hexafluorobutyl methacrylate.

[0023] Preferably, the crosslinking monomer includes, but is not limited to, any one of glycidyl methacrylate, hydroxyethyl methacrylate, and methacrylamide.

[0024] Preferably, the soft monomer includes, but is not limited to, any one of ethyl methacrylate, butyl methacrylate, isooctyl methacrylate, isodecanyl methacrylate, methacrylic acid, octadecyl methacrylate, and lauryl methacrylate.

[0025] More preferably, the fluorinated monomer is hexafluorobutyl methacrylate, the crosslinking monomer is glycidyl methacrylate, the soft monomer is octadecyl methacrylate, and the phosphorus-nitrogen synergistic acrylate monomer is PPN. The structural formula of the phosphorus-nitrogen fluorine polyacrylate water-repellent and flame-retardant finishing agent synthesized from the above monomers is as follows:

[0026]

[0027] The values ​​of x, y, and m range from 1 to 12000, and the value of z ranges from 0 to 12000.

[0028] This invention provides a method for preparing the above-mentioned phosphorus-nitrogen-fluorine polyacrylate water-repellent and flame-retardant finishing agent, comprising the following steps: dissolving the above-mentioned phosphorus-nitrogen synergistic acrylate monomer, fluorine-containing monomer, crosslinking monomer, and soft monomer in a solvent, reacting at 20-90°C for 2-24 hours, and after the reaction is completed, obtaining a phosphorus-nitrogen-fluorine polyacrylate water-repellent and flame-retardant solution, and purifying it to obtain the phosphorus-nitrogen-fluorine polyacrylate water-repellent and flame-retardant finishing agent.

[0029] Preferably, the mass ratio of the phosphorus-nitrogen synergistic acrylate monomer to the fluorinated monomer, crosslinking monomer, and soft monomer is 1-50:1-50:1-50:0-50.

[0030] Preferably, the solvent includes, but is not limited to, toluene, ethyl acetate, tetrahydrofuran, and 1,4-dioxane.

[0031] More preferably, the solvent is tetrahydrofuran.

[0032] Preferably, the purification method includes, but is not limited to, any one of distillation, recrystallization, and antisolvent crystallization.

[0033] The present invention also provides the application of the above-mentioned phosphorus-nitrogen-fluorine-containing polyacrylate water-repellent and flame-retardant finishing agent in water-repellent and flame-retardant fabrics and papers.

[0034] This invention synthesizes a novel phosphorus-nitrogen synergistic flame retardant by reacting the phosphorus-based flame retardant DOPO, which is not commonly used in flame-retardant finishing of fabrics, with amine compounds through a low-temperature and mild reaction method. In order to improve the durability of the flame retardant and the functionality of the finishing agent, acrylate units are introduced into the structure of the flame retardant to synthesize a phosphorus-nitrogen synergistic acrylate monomer. The monomer is then subjected to one-pot solution polymerization with fluorinated monomers, crosslinking monomers, and soft monomers to prepare a finishing agent with both flame-retardant and water-repellent functions, which can be applied to substrates such as cotton fabrics and paper.

[0035] Beneficial effects

[0036] (1) The phosphorus and nitrogen synergistic acrylate monomer in this invention is halogen-free, has excellent flame retardant effect, is simple to manufacture, and meets environmental protection requirements.

[0037] (2) In this invention, phosphorus and nitrogen synergistic acrylate monomer flame retardant and acrylate monomer form a copolymer in the form of graft block, which increases the durability of the flame retardant and improves the functionality of the finishing agent and its chemical bonding to the substrate.

[0038] (3) The phosphorus-nitrogen synergistic acrylate monomer flame retardant of the present invention uses the synergistic flame retardant effect of phosphorus and nitrogen elements, which improves the flame retardant effect of the finishing agent, reduces the amount of flame retardant used in the finishing agent, and reduces the cost of flame retardant materials. Attached Figure Description

[0039] Figure 1 A schematic diagram of the preparation process of phosphorus and nitrogen synergistic acrylate monomers in Example 1.

[0040] Figure 2 The phosphorus and nitrogen synergistic acrylate monomer in Example 1 1 H NMR spectrum.

[0041] Figure 3 A schematic diagram of the preparation process of the phosphorus-nitrogen-fluorine-containing polyacrylate water-repellent and flame-retardant finishing agent in Example 2.

[0042] Figure 4 The phosphorus-nitrogen-fluorine-containing polyacrylate water-repellent and flame-retardant finishing agent in Example 6 1 H NMR spectrum.

[0043] Figure 5The phosphorus-nitrogen-fluorine-containing polyacrylate water-repellent and flame-retardant finishing agent in Example 6 31 P NMR spectrum.

[0044] Figure 6 The phosphorus-nitrogen-fluorine-containing polyacrylate water-repellent and flame-retardant finishing agent in Example 6 19 F NMR spectrum.

[0045] Figure 7 The infrared spectrum of the phosphorus-nitrogen-fluorine-containing polyacrylate water-repellent and flame-retardant finishing agent in Example 6 is shown.

[0046] Figure 8 The TGA data (A) and DTG data (B) are for cotton fabric and pure cotton fabric treated with the finishing agent of Example 6.

[0047] Figure 9 The peak heat release (A) and total heat release (B) of cotton fabric and pure cotton fabric treated with the finishing agent of Example 6 are shown.

[0048] Figure 10 The Raman spectrum of carbon residue on pure cotton fabric after cone calorimetry testing.

[0049] Figure 11 The image shows the Raman spectrum of the carbon residue on the cotton fabric treated with the finishing agent of Example 6 after cone calorimetry testing. Detailed Implementation

[0050] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0051] Example 1

[0052] In this embodiment, a phosphorus-nitrogen synergistic flame-retardant acrylate monomer, 2-(((4-(6-oxodibenzo[c,e][1,2]oxaphosphon-6-yl)piperazin-1-yl)(phenyl)phosphonyl)oxy)ethyl methacrylate, denoted as PPN, was synthesized using DOPO, phenylphosphonyl dichloro, piperazine, and hydroxyethyl methacrylate (HEMA) as raw materials. The preparation process is as follows: Figure 1 As shown, the specific steps are as follows:

[0053] (1) In a 500 ml three-necked flask (equipped with a constant pressure funnel), DOPO (21.62 g, 100 mmol) and piperazine (25.84 g, 300 mmol) were added. The flask was purged with nitrogen under vacuum and dissolved in dichloromethane (180 ml). Triethylamine (12.14 g, 120 mmol) and carbon tetrachloride (18.46 g, 120 mmol) were slowly added dropwise through the constant pressure funnel at 0 °C. After the addition was complete, the mixture was reacted at room temperature for 12 h. After removing the organic solvent, the mixture was washed twice with deionized water (1000 ml), filtered, and dried to obtain a white solid 6-(piperazin-1-yl)dibenzo[c,e][1,2]oxaphosphine-6-oxide, denoted as PN. The yield was 67%.

[0054] (2) In a 250 ml three-necked flask (equipped with a constant pressure funnel), phenylphosphamide dichloride (9.75 g, 50 mmol) was dissolved in dichloromethane (50 ml). Hydroxyethyl methacrylate (6.51 g, 50 mmol) and triethylamine (6.07 g, 60 mmol) were slowly added dropwise through the constant pressure funnel at 0 °C. After the addition was complete, the reaction was allowed to proceed at room temperature for 4 h. Then, PN (15.01 g, 50 mmol) in dichloromethane (150 ml) was added dropwise through the constant pressure funnel at 0 °C. After the addition was complete, the reaction was allowed to proceed at room temperature for 12 h. The mixture was filtered to obtain a yellow liquid, which was washed with saturated sodium bicarbonate solution and saturated brine. After drying with anhydrous sodium sulfate to remove the organic solvent, a yellow viscous liquid was obtained. This liquid was purified by silica gel column chromatography using petroleum ether:ethyl acetate = 2:1 as the mobile phase. A white viscous solid, namely the phosphorus-nitrogen synergistic acrylate monomer (denoted as PPN), was obtained in a yield of 44%.

[0055] Figure 2 For phosphorus and nitrogen synergistic acrylate monomer PPN 1 The 1H NMR spectrum shows that the number and chemical shifts of all hydrogen atoms in the spectrum correspond perfectly to the number and chemical shifts of hydrogen atoms in the target compound, proving that the obtained compound was successfully synthesized.

[0056] Example 2

[0057] In this embodiment, the above-mentioned PPN monomers are synthesized into a phosphorus-nitrogen-fluorine polyacrylate water-repellent and flame-retardant finishing agent by solution polymerization with glycidyl methacrylate (GMA), octadecyl methacrylate (SMA), and hexafluorobutyl methacrylate (HFBMA). The mass ratio of phosphorus and nitrogen synergistic acrylate monomers, hexafluorobutyl methacrylate, glycidyl methacrylate, and octadecyl methacrylate is 30:40:10:20. The preparation process is as follows: Figure 3The specific method is as follows: Under nitrogen protection, hexafluorobutyl methacrylate (1.6 g, 6.40 mmol), glycidyl methacrylate (0.4 g, 2.81 mmol), octadecyl methacrylate (0.8 g, 2.36 mmol), and PPN (1.2 g, 2.17 mmol) were added. 20 ml of anhydrous tetrahydrofuran was added to dissolve the solid, and the temperature was raised to 70 °C. A tetrahydrofuran solution of azobisisobutyronitrile (0.12 g, 0.73 mmol) in 10 ml was slowly added dropwise through a constant pressure funnel. The mixture was refluxed at 70 °C for 24 h. The reaction was then stopped, and the reaction solution was slowly added to a mixture of methanol and water (V_methanol:V_water = 1:1). A white solid precipitated. The white solid was washed several times with the methanol-water mixture, dried at 65 °C for 24 h, and then weighed. A white solid product was obtained with a yield of 77%, which is a phosphorus-nitrogen-fluorine polyacrylate water-repellent flame-retardant finishing agent.

[0058] Example 3

[0059] The preparation method of the phosphorus-nitrogen-fluorine polyacrylate water-repellent and flame-retardant finishing agent in this embodiment is the same as in Example 2, except that the mass ratio of phosphorus-nitrogen synergistic acrylate monomer, hexafluorobutyl methacrylate, glycidyl methacrylate, and octadecyl methacrylate is 40:15:10:35. The yield is 88%.

[0060] Example 4

[0061] The preparation method of the phosphorus-nitrogen-fluorine polyacrylate water-repellent and flame-retardant finishing agent in this embodiment is the same as in Example 2, except that the mass ratio of phosphorus-nitrogen synergistic acrylate monomer, hexafluorobutyl methacrylate, glycidyl methacrylate, and octadecyl methacrylate is 40:30:10:20. The yield is 83%.

[0062] Example 5

[0063] The preparation method of the phosphorus-nitrogen-fluorine polyacrylate water-repellent and flame-retardant finishing agent in this embodiment is the same as in Example 2, except that the mass ratio of phosphorus-nitrogen synergistic acrylate monomer, hexafluorobutyl methacrylate, glycidyl methacrylate, and octadecyl methacrylate is 40:50:10:0. The yield is 84%.

[0064] Example 6

[0065] The preparation method of the phosphorus-nitrogen-fluorine polyacrylate water-repellent and flame-retardant finishing agent in this embodiment is the same as in Example 2, except that the mass ratio of phosphorus-nitrogen synergistic acrylate monomer, hexafluorobutyl methacrylate, glycidyl methacrylate, and octadecyl methacrylate is 50:40:10:0. The yield is 81%.

[0066] The polymer finishing agent prepared in Example 6 was subjected to...1 H NMR, 31 P NMR and 19 F NMR and infrared characterization.

[0067] Figure 4 middle 1 In the 1H NMR, the characteristic signal of double-bonded hydrogen in the monomer at 5.40-5.80 ppm completely disappeared, while the characteristic signals at other locations were basically consistent with those on the monomer, proving that the monomer had undergone a polymerization reaction to form a polymer. 31 P NMR and 19 F NMR spectrum as shown Figure 5-6 As shown, the chemical shifts of its fluorine and phosphorus signals are basically consistent with the spectral signals of the raw material. Due to the low solubility of the polymer, this leads to... 19 F NMR and 31 The P NMR spectra all exhibited low spectral signal resolution. (In summary...) 1 H NMR, 31 P NMR and 19 The F NMR spectrum indicates that copolymerization has successfully occurred between the monomers.

[0068] Figure 7 The image in the middle is the infrared spectrum of the polymer. It can be seen that the characteristic absorption peak of the carbonyl stretching vibration is located at 1737 cm⁻¹. -1 Location, 1600cm -1 The characteristic absorption peaks of the double bonds on both sides disappear, at 1482 cm⁻¹. -1 1231cm -1 1105cm -1 and 838cm -1 The absorption peaks corresponding to CN, CF, P=O, and PO bonds respectively indicate that the polymer contains ester groups, fluorocarbon chains, and phosphate groups, and that the monomers have undergone polymerization.

[0069] Example 7

[0070] The preparation method of the phosphorus-nitrogen-fluorine polyacrylate water-repellent and flame-retardant finishing agent in this embodiment is the same as in Example 2, except that the mass ratio of phosphorus-nitrogen synergistic acrylate monomer, hexafluorobutyl methacrylate, glycidyl methacrylate, and octadecyl methacrylate is 15:40:10:35. The yield is 82%.

[0071] Example 8

[0072] Phosphorus- and nitrogen-fluorine-containing polyacrylate water-repellent and flame-retardant finishing agents for cotton fabrics:

[0073] The phosphorus-nitrogen-fluorine polyacrylate water-repellent and flame-retardant finishing agents prepared in Examples 2-7 were dissolved in ethyl acetate to obtain finishing agents with a concentration of 250 g / L. Cotton fabrics that had undergone pretreatment such as desizing, scouring, and bleaching were immersed in the finishing agent at a liquor ratio of 1:10 and soaked at 50°C for 2 hours. After drying, they were pre-dried in an oven at 80°C for 4-5 minutes and then baked at 170°C for 4-5 minutes. After cooling the treated cotton fabrics to room temperature, they were ready for use to obtain cotton fabrics with water-repellent and flame-retardant functions.

[0074] Characterization and Testing: The cotton fabrics treated with the phosphorus-nitrogen-fluorine-containing polyacrylate water-repellent and flame-retardant finishing agent were subjected to the following tests, and the test results are shown below. Untreated pure cotton fabric (CF) was set as a control group.

[0075] (1) Limiting Oxygen Index Test

[0076] Using a NETZSCH LOI901 limiting oxygen index tester, several samples measuring 125mm × 55mm were tested according to the GB / T 5454-1997 standard.

[0077] (2) Water contact angle test

[0078] The hydrophobic properties of the treated cotton fabric were evaluated by measuring the contact angle. Five samples were taken from different locations on the cotton fabric, and the contact angle was measured once at each location. The average value was then taken to obtain the contact angle.

[0079] Table 1. Test results of flame retardant and water repellent properties of cotton fabrics treated with finishing agents from different embodiments.

[0080]

[0081] The test results show that the cotton fabrics treated with the finishing agent all have different degrees of water repellency and flame retardancy. Among them, the cotton fabric treated with the finishing agent in Example 6 has the best overall water repellency and flame retardancy (water contact angle reaches 121°, LOI 26.2%).

[0082] (3) Durability test

[0083] The samples were placed in a shaker of a washing fastness tester at 49°C, using a 0.15wt% sodium dodecylbenzenesulfonate solution as the washing liquid. Each 45-minute wash corresponds to 5 washing cycles. The washing resistance of the finishing agent was evaluated by the limiting oxygen index test, vertical burning test, and water contact angle test data of the tested samples. Table 2 shows that the cotton fabric treated with the finishing agent of Example 6 (Example 6 - Cotton Fabric) exhibited good self-extinguishing properties in the vertical burning test, with a damage length of 100 mm. After 5 washing cycles, the treated cotton fabric still showed self-extinguishing properties in the vertical burning test, with the damage length increasing to 220 mm, and the water contact angle remaining above 90°, indicating a certain degree of wash resistance.

[0084] Table 2. Durability data of cotton and pure cotton fabrics treated with the finishing agent of Example 6.

[0085]

[0086] (4) Fabric tensile strength test

[0087] Using the ASTM D5034-2013 standard, 15 samples each with a size of 150mm × 100mm were taken in the warp and weft directions and tested at a tensile speed of 100mm / s under a preset tension of 0.2N.

[0088] Table 3. Tensile strength data of cotton fabrics and pure cotton fabrics treated with the finishing agent of Example 6.

[0089]

[0090] As shown in Table 3, the warp and weft breaking strengths of the pure cotton fabric are 183 N and 170 N, respectively, and the tensile strains are 12.9% and 15.35%. In contrast, the warp and weft breaking strengths of the cotton fabric treated in Example 6 are 228 N and 192 N, respectively, and the tensile strains are 9.76% and 11.2%. Compared with the original cotton fabric, the breaking strength is improved to a certain extent, while the tensile strain is reduced to a certain extent. It is speculated that this is because the functional monomer glycidyl methacrylate in the polymer, after being treated onto the cotton fabric, makes the cross-linking between cellulose fibers more compact, thereby increasing the strength of the cotton fabric and reducing the deformation properties of cellulose fibers.

[0091] (5) Fabric air permeability test

[0092] Using the GB / T5453-1997 standard, five 100mm × 100mm samples were clamped onto a sample platform and tested under a pressure difference of 200 Pa using a test area of ​​20 cm². 2 The test was conducted using a circular vent, and the average airflow rate was recorded.

[0093] Table 4 shows the air permeability analysis data of cotton fabrics and pure cotton fabrics treated with the finishing agent of Example 6.

[0094] sample Breathability (mm / s) pure cotton fabric 98.72 Example 6 - Cotton Fabric 75.01

[0095] As can be seen from Table 4, the treated cotton fabric has poorer air permeability compared to pure cotton fabric. This is because the coating fills the gaps between the fibers, affecting the airflow between the fibers and resulting in decreased air permeability.

[0096] (6) Thermal stability test

[0097] Using a Netzsch TGA 209F1 system, 1-4 mg of sample was weighed and the temperature was increased from 30 °C to 900 °C under nitrogen atmosphere at a heating rate of 10 kJ / min.

[0098] from Figure 8 As can be seen from AB, the cotton fabric treated with the finishing agent of Example 6 exhibits two stages of weight loss. It begins to decompose at 287.8℃. The first stage of degradation is mainly caused by the thermal degradation of ester bonds in the polymer, occurring between 287℃ and 364℃. Then, as the temperature continues to rise, the polymer enters the next stage of thermogravimetric analysis (TGA). The weight loss in this stage is mainly due to the breakage of the phenanthrene ring structure, the opening of P=O and PO chemical bonds, and the generation of PO· and PO2· free radicals. These free radicals capture the carbon free radicals generated during degradation, preventing further degradation of the molecular chain and the formation of a carbon layer. Therefore, the residual carbon content of the cotton fabric treated with the finishing agent prepared in Example 6 is higher than that of pure cotton fabric, at 14.41%. The DTG curve shows that the entire thermal degradation process of the treated cotton fabric is earlier than that of the original cotton fabric. The main weight loss range of the treated cotton fabric is concentrated between 280℃ and 410℃. The TGA of the cotton fabric treated with the finishing agent of Example 6 within this temperature range... max and R Tmax The values ​​were 296.5℃ and 36.88% / min, respectively. Its T... Max and R Tmax They are all smaller than pure cotton fabrics. This may be because the phosphoric acid and polyphosphoric acid produced by the thermal degradation of phosphorus compounds promote the dehydration of cotton fabrics and the formation of a carbon layer, which prevents the cotton fabrics from further degradation.

[0099] (7) Cone calorimetry test

[0100] Using a cone calorimeter from Fire Testing Technology, four pieces of material measuring (100×100×3) mm were cut and stacked. 3 The sample at 35KW / m 2 Or 50KW / m 2 The test was conducted under the irradiation intensity.

[0101] Table 5. Cone calorimetry test data of cotton fabrics and pure cotton fabrics treated with the finishing agent of Example 6.

[0102]

[0103] From Table 5 and Figure 9 As can be seen from AB, the peak heat release rate (pHRR) and total heat release (THR) of the cotton fabric treated with the finishing agent of Example 6 are 138.29 kW / m². 2 and 8.05 MJ / m 2 The heat release during the combustion of cotton fabric was reduced by 43% and 52% respectively, significantly lower than that of pure cotton fabric. This indicates that the finishing agent can reduce the heat release during the combustion process of cotton fabric. The fire growth rate (FGR) and CO2 / CO ratio are parameters for measuring the flammability of materials; the lower these values, the better the fire resistance of the material. The FGR and CO2 / CO ratio of the cotton fabric treated in Example 6 were 2.27 kW / (m³). 2 The flame retardancy of the treated cotton fabric was 10.55 kg / kg, which is significantly lower than that of pure cotton fabric. These data indicate that the cotton fabric treated with the finishing agent has good flame retardancy.

[0104] (8) Raman test

[0105] The carbon residue of the CCT sample was tested using a Thermo Fisher Scientific DXR laser Raman spectrometer, according to I D / I G The graphitization degree of the sample carbon residue was analyzed using a laser light source of 532 nm, and the testing range was 800-2000 cm⁻¹. -1 .

[0106] Figure 10 , Figure 11 The figures show Raman spectral data of residual char after cone calorimetry testing of pure cotton fabric and cotton fabric treated with the finishing agent of Example 6, respectively. As can be seen from the figures, the I... D / I G The carbon residue I of the cotton fabric treated with the finishing agent of Example 6 was 1.84. D / I G The values ​​are 1.03, which is much lower than the value for pure cotton fabrics, typically I D / I G The smaller the value, the higher the degree of graphitization. This proves that the finishing agent can promote the formation of a dense carbon layer in cotton fabrics during combustion, which is consistent with the condensed phase flame retardant mechanism of phosphorus-based flame retardants.

Claims

1. A phosphorus-nitrogen synergistic acrylate monomer, characterized in that, The structure of the phosphorus-nitrogen synergistic acrylate monomer is shown in formula (1): Wherein, R1 includes any one of methoxy, ethoxy, hydroxy, phenyl, phenoxy, and spirocyclic hydrocarbons; R2 includes C2 to C6 alkylene compounds; and DOPO is 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

2. The phosphorus-nitrogen synergistic acrylate monomer according to claim 1, characterized in that, The phosphorus-nitrogen synergistic acrylate monomer is prepared by reacting a DOPO-containing amine compound with a phosphoric acid chloride-containing methacrylate compound; wherein the structure of the DOPO-containing amine compound is shown in formula (II): The structure of the phosphoryl chloride-containing methacrylate compound is shown in (III):

3. A method for preparing the phosphorus-nitrogen synergistic acrylate monomer as described in claim 2, comprising: The DOPO-containing amine compound and the phosphoric acid chloride-containing methacrylate compound are dissolved in a solvent and reacted at -10 to 0°C for 2 to 24 hours to separate and obtain the phosphorus-nitrogen synergistic acrylate monomer.

4. The preparation method according to claim 3, characterized in that, The molar ratio of the DOPO-containing amine compound to the phosphoric acid chloride-containing methacrylate compound is 1:1 to 2; the volume-to-mass ratio of the solvent to the total amount of the DOPO-containing amine compound and the phosphoric acid chloride-containing methacrylate compound is 2 to 10 ml / g.

5. The preparation method according to claim 3, characterized in that, The solvent includes any one of substituted alkanes, esters, ethers, and nitrile compounds.

6. A phosphorus- and nitrogen-fluorine-containing polyacrylate water-repellent and flame-retardant finishing agent, characterized in that, The phosphorus-nitrogen-fluorine polyacrylate water-repellent and flame-retardant finishing agent is prepared by reacting the phosphorus-nitrogen synergistic acrylate monomer with fluorine-containing monomer, crosslinking monomer, and soft monomer as described in claim 1.

7. The phosphorus-containing nitrogen-fluorine polyacrylate water-repellent and flame-retardant finishing agent according to claim 6, characterized in that, The fluorinated monomer includes any one of trifluoroethyl methacrylate, 2-(perfluorooctyl)ethyl methacrylate, 2-(perfluorohexyl)ethyl methacrylate, 2-(perfluorobutyl)ethyl methacrylate, 1,1,1,3,3,3-hexafluoroisopropyl isobutylene methacrylate, and hexafluorobutyl methacrylate; the crosslinking monomer includes any one of glycidyl methacrylate, hydroxyethyl methacrylate, and methacrylamide; the soft monomer includes any one of ethyl methacrylate, butyl methacrylate, isooctyl methacrylate, isodecanyl methacrylate, methacrylic acid, octadecyl methacrylate, and lauryl methacrylate.

8. A method for preparing a phosphorus-containing nitrogen-fluorine polyacrylate water-repellent and flame-retardant finishing agent as described in claim 6, comprising the following steps: Phosphorus and nitrogen synergistic acrylate monomers, fluorine-containing monomers, crosslinking monomers, and soft monomers are dissolved in a solvent and reacted at 20–90°C for 2–24 hours. After the reaction is completed, a water-repellent and flame-retardant solution of phosphorus, nitrogen, and fluorine polyacrylate is obtained. After purification, a water-repellent and flame-retardant finishing agent of phosphorus, nitrogen, and fluorine polyacrylate is obtained.

9. The preparation method according to claim 8, characterized in that, The feed mass ratio of the phosphorus-nitrogen synergistic acrylate monomer to the fluorinated monomer, crosslinking monomer, and soft monomer is 1-50:1-50:1-50:0-50.